2021
DOI: 10.1590/1807-1929/agriambi.v25n12p840-846
|View full text |Cite
|
Sign up to set email alerts
|

Maize crop yield in function of salinity and mulch

Abstract: Irrigation with saline water affects the agronomic performance of the maize crop; however, the use of vegetal mulch may mitigate salt stress and promote an increase in yield. In this way, this study aimed to evaluate the grain yield of the maize plants submitted to different water salinity levels in the presence and absence of mulch. The experiment was conducted in a randomized block design arranged in a 2 × 2 factorial scheme. The first factor was the salinity of the irrigation water (1.0 and 4.0 dS m-1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
2
10
0
2
Order By: Relevance
“…These results are consistent with those of Goes et al (2021), who found that an increase in the concentration of salts in irrigation water compromised the emission of lima bean leaves.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with those of Goes et al (2021), who found that an increase in the concentration of salts in irrigation water compromised the emission of lima bean leaves.…”
Section: Resultssupporting
confidence: 93%
“…The use of saline water in agriculture reduces the osmotic and water potential of plants, which consequently decreases the availability of water, absorption, and transport of essential nutrients for plant growth. This, in turn, leads to nutritional imbalance, affecting the physiological functions and productive potential of cultivated plants (Lima et al, 2021;Sousa et al, 2021;Costa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kandil et al (2020) verified an increase in the length of maize cobs when irrigated with water of lower salinity and fertilized with organic compost in the form of humic acid, with an average of 17.8 cm, a value higher than that obtained in the present study. A study by Costa et al (2021), under field conditions, showed lower performance in terms of ear length in areas irrigated with increased saline water.…”
Section: Resultsmentioning
confidence: 96%
“…Favarato et al (2016) obtained commercial cob diameters in maize crops with the application of organic material in topdressing, similar to crops with NPK in mineral form. Regarding the observed reductions, the salt content of the organic fertilizers may have potentiated the saline effect of irrigation water (Souza et al, 2019), causing lower water uptake owing to osmotic stress, which may have compromised the processes of nutrient uptake, cell division, and expansion, thus causing reduction in cob diameter (Costa et al, 2021;Sousa et al, 2021). Contrary to these results, Rodrigues et al (2020) found no influence of salt on the cob diameter of maize under the same edaphic and climatic conditions as used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation